Determinants of duration of unemployment among first-time job seekers in Bail Province - Adiyadnya, Made Santana Putra; Marhaeni, Anak Agung Istri Ngurah; Suasih, Ni Nyoman Reni; Mustika, Made Dwi Setyadhi (Edelweiss Applied Science and Technology, 2025)
The purpose of this research is to determine the impact of social and economic factors, circular migration, psychology, and the adoption of science and technology on the length of unemployment among first-time job seekers. The participants in this study were all 20–30-year-old workers in Denpasar City, Badung Regency, and Gianyar Regency. This study used an accidental sampling technique and snowball sampling. Next, proportionate stratified techniques were used to gain participants according to their level of education, with a sample size of 165 respondents. An additional finding is that economic conditions do not affect the length of unemployment experienced by first-time job seekers; the adoption of science and technology does not mitigate the impact of social and psychological factors on the length of unemployment experienced by first-time job seekers; and the adoption of science and technology mitigates the impact of both economic conditions and the circular migration culture on the length of unemployment experienced by first-time job seekers. The practical implications of this research are that job seekers in Bali, in particular, can start adopting science and technology to improve the culture and economic conditions of migration circulation.